Improving Learning Outcomes of Class VII B Students of SMP Negeri 4 Kendari Material of Square and Rectangular Areas Through the Use of Class Floors - rukmini rukmini (Amanah: Jurnal Amanah Pendidikan dan Pengajaran, 2021)
This study aimed to improve the learning outcomes of class VII B students of SMP Negeri 4 Kendari in terms of square and rectangular areas through the classroom floor. This type of research is classroom action research. The study is located at SMP Negeri 4 Kendari. The research subjects were class VII.B. This research consists of 2 cycles. Each cycle includes planning, action, observation, and reflection activities. Observation and data collection were carried out by teachers and researchers with the assistance of colleagues as observers. The data collection instruments were in tests and observation sheets for teachers and students. The results showed that classroom floor media could help students understand the concept of determining the area of ​​a square and rectangle. Can be seen in cycle 2 of the student learning outcomes test. There are 32 students (91.43%) who get a score of 70 compared to cycle 1 of the student learning outcomes test; there are 25 students (71.43%) who got a score of 70. Based on research data, the use of the classroom floor as a simple learning medium in the learning process can increase the seriousness and motivation of students to take part in the learning process in class.